Musica elettronica viva: 1967-2007 - MEV 40 (New York New World Records, 2008)
Musica Elettronica Viva (MEV) was begun one evening in the spring of 1966 by Allan Bryant, Alvin Curran, Jon Phetteplace, Carol Plantamura, Frederic Rzweski, Richard Teitelbaum and Ivan Vandor in a room in Rome overlooking the Pantheon. MEV's music right from the start was also totally open, allowing all and everything to come in and seeking in every way to get out beyond the heartless conventions of contemporary music. Taking its cue from Tudor and Cage, MEV began sticking contact mics to anything that sounded and amplified their raw sounds: bed springs, sheets of glass, tin cans, rubber bands, toy pianos, sex vibrators, and assorted metal junk; a crushed old trumpet, cello and tenor sax kept us within musical credibility, while a home-made synthesizer of some 48 oscillators along with the first Moog synthesizer in Europe gave our otherwise neo-primitive sound an inimitable edge. In the name of the collectivity, the group abandoned both written scores and leadership and replaced them with improvisation and critical listening. Rehearsals and concerts were begun at the appropriate time by a kind of spontaneous combustion and continued until total exhaustion set in. It mattered little who played what when or how, but the fragile bond of human trust that linked us all in every moment remained unbroken. The music could go anywhere, gliding into self-regenerating unity or lurching into irrevocable chaos-both were valuable goals. In the general euphoria of the times, MEV thought it had re-invented music; in any case it had certainly rediscovered it. -Alvin Curran This 4-CD set, covering the years 1967â¬2007, comprises the best surviving recorded documents from four decades of performances, personally curated by its three core members-Alvin Curran, Frederic Rzewski, and Richard Teitelbaum. As such, it is an invaluable historical anthology of one of the pioneering and truly legendary exponents of live-electronic music